2013
DOI: 10.1074/jbc.m112.421669
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 779 in Fibroblast Growth Factor Receptor 1 and 2 by Protein Kinase Cϵ Regulates Ras/Mitogen-activated Protein Kinase Signaling and Neuronal Differentiation

Abstract: Background:The FGF receptors (FGFRs) regulate pleiotropic (diverse) cellular responses. Results: Serine 779 phosphorylation of FGFR1 and 2 by PKC⑀ promotes maximal Ras/MAPK signaling and neuronal differentiation. Conclusion:The FGFRs quantitatively control signal transduction via receptor serine phosphorylation. Significance: Receptor tyrosine kinases couple to specific downstream signaling pathways via phosphoserine docking sites to control pleiotropic cellular responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The activation of FGFR2 has been shown to regulate cell differentiation via PKC. 41,42 Interestingly, the activation of PKC has been shown to be involved in the regulation of blastocoel formation during mouse preimplantation development, 28,43 which is in accordance with our observation that the inhibition of PKC significantly suppressed the formation of expanded blastocysts. More importantly, p38 regulates cavitation and the function of tight junctions, which affects the expanded formation of the blastocyst.…”
supporting
confidence: 80%
“…The activation of FGFR2 has been shown to regulate cell differentiation via PKC. 41,42 Interestingly, the activation of PKC has been shown to be involved in the regulation of blastocoel formation during mouse preimplantation development, 28,43 which is in accordance with our observation that the inhibition of PKC significantly suppressed the formation of expanded blastocysts. More importantly, p38 regulates cavitation and the function of tight junctions, which affects the expanded formation of the blastocyst.…”
supporting
confidence: 80%
“…Members of the FGFR family play a key role in the regulation of cell proliferation, differentiation, and in the regulation of embryonic development. Previous studies have reported the relationship between FGFR2 gene and the regulation of ERK gene (Schuller et al, 2008;Lonic et al, 2013). Evidence from animal studies demonstrated that ERK gene may have a regulatory function to swallowing reflex in rats (Tsujimura et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…morphological maturation phenotype). Indeed, upon knocking-down of FGFR2, we may not only affect its interaction with NEGR1, but also with other molecules involved in its downstream signalling ( Williams et al , 1994 ; Lonic et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%